2022
DOI: 10.3389/frsfm.2022.835057
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Detection of Ochratoxin A Using Aptamer as Recognition Probe at Liquid Crystal-Aqueous Interface

Abstract: Aqueous interfaces of stimuli-responsive, thermotropic nematic liquid crystals (LC) have been utilized in the design of biosensing platforms for a range of analytes. Owing to the orientational changes in LC, these interfaces can easily report aptamer-target binding events at the LC-aqueous interface. We demonstrate a label-free, simple and robust technique for the detection of Ochratoxin A (OTA) using aptamer as the recognition probe. The self-assembly of CTAB (cetyltrimethylammonium bromide; cationic surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…LCs are stimuli-responsive materials that can be confined within films, shells, and spherical microdroplets. , The ordering of LC molecules at the interface of the surrounding aqueous phase is sensitive to the presence of interfacial adsorbates. For the first time, Lavrentovich et al showed that nematic drops show spontaneous transitions between different topological states . The equilibrium states are defined by the presence of topological defects that are formed as a result of the spherical confinement and anchoring conditions .…”
Section: Introductionmentioning
confidence: 99%
“…LCs are stimuli-responsive materials that can be confined within films, shells, and spherical microdroplets. , The ordering of LC molecules at the interface of the surrounding aqueous phase is sensitive to the presence of interfacial adsorbates. For the first time, Lavrentovich et al showed that nematic drops show spontaneous transitions between different topological states . The equilibrium states are defined by the presence of topological defects that are formed as a result of the spherical confinement and anchoring conditions .…”
Section: Introductionmentioning
confidence: 99%